Design, synthesis and activity studies of antifreeze peptide derived from type I shorthorn sculpin - Asmawi, Azren Aida (2015)
Freezing water is rapidly fatal to most organisms as it deprives biological reactions of the aqueous medium they require due to the formation of ice crystals. However, a number of structurally different classes of antifreeze proteins (AFPs) allow cold-adapted organisms to survive in a sub-zero environment by inhibiting the growth of the ice crystals; phenomenon’s known as Thermal Hysteresis (TH) and Ice Recrystallization Inhibition (IRI). In this work,we study on the antifreeze activity of short protein fragments (peptides) instead of the whole protein and analyse their functional properties. These peptides are characterized by several fragments isolated from different regions of type I shorthorn sculpin, Myoxocephalus scorpius (SS-3) AFP; namely SC-C, SC-N, SC-M and two modified peptides (SC-MM and SC-NM). The peptides were predicted by PEP-FOLD to be an amphipathic α-helix with one face entirely composed of Alanine and other hydrophobic residues, assumed to be responsible for antifreeze activity. The peptides with more than 90% purity were synthesized using solid phase peptide synthesis with immobilized Fmoc-amino acids on rink amide resins as a starting point. Their antifreeze activity and interactions with water and ice crystals are analysed using osmometry techniques. It is shown that only peptide SC-C has no IRI activity, while peptide SC-N, SC-M and both modified peptides (SC-MM and SC-NM) have an activity of about 25 – 45% of the native protein activity. These four peptides, which exhibit hexagonal shapes of ice crystal morphology in aqueous solution, indicate the presence of moderate antifreeze activity. The relationship between peptide activity and structure is explored by CD and FTIR spectroscopy. All designed peptides show moderate helical content (24-37%) concordant with FTIR results due to the presence of amide I at 1650 – 1658 cm-1 and amide II at 1545 cm-1, which are referred to be the characteristic of α- helices. Peptides SC-MM, SC-M and SC-NM demonstrate the highest activity that correlates with helicity content and hydrophobicity distribution in their structure. Furthermore, these peptides have been proved to be non-cytotoxic on 3T3 cell line with IC50 value >100 μg/mL and have a positive impact on ice crystal growth in ice cream mixes. Hence, this approach can create very promising possibilities for developing commercial potential peptide with antifreeze activity at a low cost.